PENGARUH PENJUALAN DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - amran manurung (Visi Sosial Humaniora, 2021)
This study aims to know the effect of sales and account receivables turnover on profitability in manufacturing companies in the consumer goods and industrial sector listed on Indonesian stock exchange for 2017-2019 period. The independent variables in the study are sales and accounts receivable turnover. The dependent variable was profitability. The sample in this study was manufacturing companies in the consumer goods and industrial sector listed on the Indonesian stock exchange from 2017-2019, namely 27 companies. They were taken by purposive sampling technique and 81 datawere taken. The method in analyzing data by using multiple linear regression. The results of the study showed that the influence of sales did not have effect on profitability, while the influence of account receivables turnover have significant effect on profitability. Simultaneously the influence of sales and accounts receivable turnover has significant effect on profitability.